2016
DOI: 10.1186/s12876-016-0544-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of race and ethnicity on mortality and healthcare utilization in alcoholic hepatitis: a cross-sectional study

Abstract: BackgroundAlcoholic Hepatitis (AH) is major source of alcohol-related mortality and health care expenditures in the United States. There is insufficient information regarding the role of race and ethnicity on healthcare utilization and outcomes for patients with AH. We aimed to determine whether there are racial/ethnic differences in resource utilization and inpatient mortality in patients hospitalized with AH.MethodsWe analyzed data from the Nationwide Inpatient Sample (NIS), years 2008–2011. We calculated de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…This method has been used in previous studies to define decompensation. 28,32 Sensitivity analyses were also performed using alternate definitions of decompensation, based on ICD-9-CM codes for decompensation events (A. Baveno Stage 3/4; B. Ascites, hepatic encephalopathy, or bleeding esophageal varies; C. B + nonbleeding varices; D. C + hepatorenal syndrome or SBP). To explore whether cirrhosis-related procedures differed by gender, we also utilized validated ICD-9-CM procedure codes to identify paracentesis, thoracentesis, and transjugular intrahepatic portosystemic shunt (TIPS) procedures, and the procedure-based CCS to identify upper endoscopies.…”
Section: Variablesmentioning
confidence: 99%
“…This method has been used in previous studies to define decompensation. 28,32 Sensitivity analyses were also performed using alternate definitions of decompensation, based on ICD-9-CM codes for decompensation events (A. Baveno Stage 3/4; B. Ascites, hepatic encephalopathy, or bleeding esophageal varies; C. B + nonbleeding varices; D. C + hepatorenal syndrome or SBP). To explore whether cirrhosis-related procedures differed by gender, we also utilized validated ICD-9-CM procedure codes to identify paracentesis, thoracentesis, and transjugular intrahepatic portosystemic shunt (TIPS) procedures, and the procedure-based CCS to identify upper endoscopies.…”
Section: Variablesmentioning
confidence: 99%
“…Cirrhosis and its decompensation (hepatorenal syndrome, jaundice, hepatic encephalopathy, ascites, variceal bleeding, and portal hypertension) were identified through ICD-9-CM codes (Supplementary Table 1). The Baveno IV classification has been extensively used and validated in the HCUP-NIS for the reliable identification of liver cirrhosis and assessment of its severity [28]. Finally, hospital characteristics that could impact outcomes were determined from the dataset and included hospital region (Northeast, South, Midwest and West), and hospital teaching status (rural, urban-nonteaching and urbanteaching).…”
Section: Study Population and Variablesmentioning
confidence: 99%
“…The main issue regards the long term management of the complications of portal hypertension. Previous published data have shown that Latinos are more likely to visit the ED and are more often admitted through the ED for alcohol related issues[ 22 ]. Similarly, our study showed that Latinos present more frequently at the ED and are hospitalized more often compared to Caucasians for alcohol related issues, but also present more frequently severe complications of portal hypertension.…”
Section: Discussionmentioning
confidence: 99%